2023
DOI: 10.2147/jir.s393850
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment with Eupatilin Attenuates Inflammation and Coagulation in Sepsis by Suppressing JAK2/STAT3 Signaling Pathway

Abstract: Sepsis is an aggressive and life-threatening organ dysfunction induced by infection. Excessive inflammation and coagulation contribute to the negative outcomes for sepsis, resulting in high morbidity and mortality. In this study, we explored whether Eupatilin could alleviate lung injury, reduce inflammation and coagulation during sepsis. Methods: We constructed an in vitro sepsis model by stimulating RAW264.7 cells with 1 μg/mL lipopolysaccharide (LPS) for 6 hours. The cells were divided into control group, LP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 66 publications
1
3
0
Order By: Relevance
“…We found that EUP significantly inhibited activation of MAPK and NF-κB cascades. Similar to our findings, recent studies reported that EUP alleviated septic lung injury by reducing cytokine production and macrophage infiltration [ 46 , 47 ]. EUP inhibited pro-inflammatory cytokine production in LPS-treated macrophages by suppressing the NF-κB pathway [ 48 ].…”
Section: Discussionsupporting
confidence: 93%
“…We found that EUP significantly inhibited activation of MAPK and NF-κB cascades. Similar to our findings, recent studies reported that EUP alleviated septic lung injury by reducing cytokine production and macrophage infiltration [ 46 , 47 ]. EUP inhibited pro-inflammatory cytokine production in LPS-treated macrophages by suppressing the NF-κB pathway [ 48 ].…”
Section: Discussionsupporting
confidence: 93%
“…Eupatilin (5,7-dihydroxy-3′,4′,6-trimethoxyflavone) ( Figure 1 ) is the primary flavonoid extracted from the herbaceous perennial plant Artemisia argyi of the Asteraceae family with pharmacological potential due to its anti-cancer, anti-oxidant and anti-inflammatory properties [ 132 ]. Eupatilin’s biological activities have been shown to be mediated by the regulation of several signaling pathways, including NF-κB, MAPK, Nrf2 and JAK2/signal transducer and activator of transcription (STAT) 3, through which the compound has been reported to suppress allergic inflammatory responses, lung injury in sepsis and ovalbumin-induced asthma [ 133 , 134 , 135 , 136 ]. Furthermore, eupatilin has been reported to exert chondroprotective effects in IL-1β-stimulated human OA chondrocytes in vitro and antinociceptive and chondroprotective properties in a rat model of OA in vivo by downregulating phosphorylated levels of JNK, oxidative damage and catabolic activity [ 137 ].…”
Section: Plant-derived Compounds With a Reported Senotherapeutic Acti...mentioning
confidence: 99%
“…Leukocyte-generated thrombin can activate PARs found on both ECs and leukocytes, prompting ECs to release inflammatory factors such as IL-6. Thrombin's effect on ECs increases the expression of selectin E and P on the EC surface, thereby augmenting leukocyte adhesion to ECs and facilitating leukocyte exudation and chemotaxis [199]. Conversely, inflammatory factors and chemokines can attract a substantial number of inflammatory cells to accumulate at the site of inflammation, which produce numerous cytokines within the inflamed area, culminating in a cytokine storm.…”
Section: Interaction Between Endothelial Cells and Leukocytesmentioning
confidence: 99%